Pengaruh Pemahaman Keislaman terhadap Kedisiplinan Pelaksanaan Sholat Jum’at Pegawai Pasar: Analisis Korelasional di Kota Banjar - krisdayanti, devi; Pribadi, Pandu; Supriatna, Nana; Irfan Marjuqi, Adi; Sulaeman, Maman (TarbiyahMU, 2025)
Friday Prayer is a mandatory act of worship that holds both spiritual and social significance for Muslims, particularly for men. However, in practice, there are still phenomena of low discipline in performing Friday Prayer among market employees and traders due to the intensity of economic activities. This study aims to describe the level of Islamic understanding among market employees, to examine the discipline of Friday Prayer observance, and to analyze the influence of Islamic understanding on such discipline. The research method used is quantitative correlational with a sample of 50 employees of Banjar City Market selected through stratified random sampling. Data were collected using questionnaires and analyzed with the help of SPSS through prerequisite tests (normality, linearity, and heteroscedasticity) as well as the Spearman Rank correlation test. The findings show that employees’ Islamic understanding is in the high category (91.2%), as is their level of discipline in performing Friday Prayer (94%). The Spearman correlation test produced a coefficient value of 0.567 with a significance level of 0.000 < 0.01, indicating a positive and significant influence between Islamic understanding and discipline in performing Friday Prayer. Thus, the higher the employees’ Islamic understanding, the more disciplined they are in observing Friday Prayer. These findings support structural functionalism theory, which emphasizes the role of religion in maintaining social order, while also providing practical implications for market management to facilitate religious practices amidst intensive economic activities.